More or less likely to offend? Young adults with a history of identified developmental language disorders. Issue 2 (21st November 2017) - Winstanley, Maxine; Webb, Roger T.; Conti‐Ramsden, Gina
Abstract: Background: There is now substantial literature demonstrating that a disproportionate number of young people who come into contact with youth justice services evidence unidentified language difficulties. These young people, therefore, have received little or no professional input in this area. Conversely, there is a dearth of research pertaining to criminality outcomes among those individuals with identified developmental language disorders (DLD) who have received such interventions. Aims: To examine police‐initiated contact and substance use outcomes of young adults with a history of identified DLD versus age‐matched peers (AMP). Additionally, self‐reported rule breaking behaviours and aggression are considered. We hypothesize that early identification/intervention reduces engagement with risky behaviour such as substance and alcohol use as well as offending‐related behaviours. Methods & Procedures: Adversarial police‐initiated contacts were examined in 84 young adults with a history of DLD and 88 AMP. Rule‐breaking and aggression were evaluated using the Achenbach Adult Self‐Report for ages 18–59 years. Outcomes & Results: Adults with a history of DLD who received targeted intervention during their school years reported less contact with their local police service compared with AMPs at age 24. Comparable proportions of both groups reported current alcohol consumption, but group differences were found relating to alcohol use. No group differences in rule‐breaking behaviours were found, but the DLD group was found to have a statistically significant higher raw score on the aggressive behaviour scale. Conclusions & Implications: There is a need for early identification of children with DLD. Early intervention aimed at ameliorating such difficulties could possibly have distal outcomes in relation to offending.